From Bali to the Gold Coast: A Comparative Study of Digital Transformation in Tourism Taxation of Indonesia and Australia - Fatmawati Zahroh; Ranjith Ihalanayake (KEUNIS, 2026)
This quantitative study examines how digital transformation, institutional capacity, and monitoring systems drive taxpayer compliance and tourism tax performance in Bali, Indonesia, and the Gold Coast, Australia, also considering the challenges posed by persistent tax leakages and uneven digital infrastructure. Low digital adoption in tourism-related sectors threatens the efficiency of their respective ecosystems and contributes to the issues caused by the consequential rise in tax expenditures for the governments. The analysis employed the Structural Equation Model (SEM), with 200 validated responses from tourism companies from both regions. The constructs’ measurement and structural invariance tests as per the model indicated their reliability and validity with decent fit indexes. Although the estimates show a direct and positive influence of digital transformation on taxpayer compliance, the moderated path of institutional capacity suggests that targeted digital interventions have greater effectiveness when aligned with certain skills, leadership, and infrastructure capabilities. Those with monitoring and anti-leakage systems have considerably lower tax leakages, implying that real-time digital verification tools can add considerable value in combating tax leakage. The increasing compliance of personnel taxpayers exerts a positive influence on tourism tax revenues, enabling a more systematic and administratively efficient tax collection. Furthermore, a multi-group analysis confirms that the Gold Coast is more affected by digital maturity and institutional capacity, compared to Bali. These findings highlight the importance of integrating digital strategies and capabilities to improve tax collection in the tourism sector.